2017
DOI: 10.15835/nbha45110361
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Curcumin on Oxidative Stress in a Model of Turpentine Induced Acute Experimental Inflammation

Abstract: Curcumin, a natural phenolic compound is an anti-tumor agent with anti-inflammatory and anti-oxidant properties. The aim of this research was to evaluate oxidative stress levels, the antioxidant activity and Curcumin concentrations by high performance liquid chromatography (HPLC) in an acute experimental inflammation induced by Turpentine oil (intramuscular 0.6 mg kg -1 body weight) and to compare a prophylactic versus a therapeutic regimen of Curcumin (oral suspension of 150 mg Curcumin kg -1 rat weight). Six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…TCDD also increased liver levels of GSH, CuZn-SOD and GSH-Px [ 77 ]. Coneac et al found that curcumin is able to reduce oxidative stress in acute experimental inflammation produced by Turpentine oil [ 78 ]. Dai et al has confirmed that curcumin could ameliorate reduced L02 cell viability, prevent oxidative stress and inhibit the rises of SOD activity and GSH level.…”
Section: Cellular and Molecular Mechanisms Of Curcumin In The Prevmentioning
confidence: 99%
“…TCDD also increased liver levels of GSH, CuZn-SOD and GSH-Px [ 77 ]. Coneac et al found that curcumin is able to reduce oxidative stress in acute experimental inflammation produced by Turpentine oil [ 78 ]. Dai et al has confirmed that curcumin could ameliorate reduced L02 cell viability, prevent oxidative stress and inhibit the rises of SOD activity and GSH level.…”
Section: Cellular and Molecular Mechanisms Of Curcumin In The Prevmentioning
confidence: 99%
“…Reactive oxygen species degrade polyunsaturated lipids, forming malondialdehyde (MDA). This stable end-product aldehyde is used as a biomarker to measure the level of oxidative stress in an organism [13][14][15].…”
Section: Introductionmentioning
confidence: 99%